Comparative evaluation of efficacy of three single file retreatment systems for removal of gutta percha and assessment of root canal transportation - An In Vitro study - K Nanda Kishore; K Madhu Varma; Girija S Sajjan; R Kalyan Satish; Raheem Mohammad; Gnana Sindhu Dutta (Wolters Kluwer Medknow Publications, 2022)
Background: In comparison to multiple file systems, recent advancements in single file retreatment systems had reduced the working time and ease of operation for clinicians. Aim: To compare the efficacy of retreatment systems compared with hand instrumentation, by evaluating their removal efficacy, time required for retreatment and assessment of canal transportation. Methods and Material: Forty premolars were instrumented using ProTaper Gold gold files. Post instrumentation, scan was taken, obturated using warm vertical compaction technique, and stored in artificial saliva for three months and randomly divided into four groups for retreatment. Hand instrumentation (Hi), Neoniti (Nn), Mtwo R (Mt), WaveOne Gold (Wg). Post retreatment, scan was taken. Teeth were sectioned longitudinally and photographed under the stereomicroscope. Retreatment time was recorded, and canal transportation was calculated. Statistical Analysis: The results were analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post hoc test at 95% confidence level. Results: The retreatment time was significantly longer in the Hi group. Within the test groups, a significantly longer time has been taken by Wg (p < 0.05) compared to Mt and Nn. There was no difference in the canal transportation between the single file systems at 3 mm, 6 mm and 9 mm from the apex, there was statistically significant higher transportation for the Hi group at 9 mm from the apex (p < 0.05). Conclusions: All techniques were effective in removal of filling material with minimal canal transportation. Wg system was shown to increased time compared to Nn and Mt systems. Hi group was slowest with maximum canal transportation at 9 mm from the apex.